2019
DOI: 10.1177/1550147719875878
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent human-centric lighting for mental wellbeing improvement

Abstract: In recent years, the main area of interest in the issue of influencing mental states of people is the impact of lighting on human beings, their wellbeing but also workplace productivity. This work discusses in detail the problem of positively influencing people using intelligent technologies, especially the role of the colors. We describe techniques and technologies needed to implement the case study of an intelligent lighting system. The system proposed can detect humans from an IP camera, find faces, and det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Other advantages include their long lifespan that ranges from 50,000 to over 100,000 h (Schratz et al 2013;Vahl, Campos, and Filho 2013), their robustness and stability independent of the amount of shifting, and a high natural colour rendering with flicker-free light. Novel LED technologies can adjust both colour temperature and light intensity due to dimmable bicolour LED lamps (Lee et al 2016;Cupkova et al 2019). The heat radiation of traditional lighting systems does not exist for LEDs, so that coolants and lubricants combined with dust cannot burn in.…”
Section: Ledmentioning
confidence: 99%
“…Other advantages include their long lifespan that ranges from 50,000 to over 100,000 h (Schratz et al 2013;Vahl, Campos, and Filho 2013), their robustness and stability independent of the amount of shifting, and a high natural colour rendering with flicker-free light. Novel LED technologies can adjust both colour temperature and light intensity due to dimmable bicolour LED lamps (Lee et al 2016;Cupkova et al 2019). The heat radiation of traditional lighting systems does not exist for LEDs, so that coolants and lubricants combined with dust cannot burn in.…”
Section: Ledmentioning
confidence: 99%
“…According to the paper, the HCL living lab experiment conducted on three groups (Alzheimer's patients, adolescents, and shift workers) showed that HCL was effective in improving depression and sleep disorders. In addition, studies by Cupkova et al [10], Figueiro et al [11], and Figueiro & Leggett [8] objectively demonstrated the life-improving impact of HCL. These studies have important implications in that they emphasize the necessity and impact of introducing HCL but are limited by a lack of management strategies for the industrial dissemination of HCL.…”
Section: Theoretical Background 21 Human Centric Lightingmentioning
confidence: 95%
“…Furthermore, HCL is regarded as a potential alternative solution to solve social issues such as energy and environmental problems [9]. Therefore, studies in this field have focused on the medical effects of HCL [8,10,11], ergonomic designs (Deli et al, 2018;Nicolantonio et al, 2020), and lifelog-based platforms for smart lighting [12,13]. Although detailed research is essential for the advancement of the HCL field, macroscopic research from the perspective of convergence studies is also necessary for the spread and revitalization of the HCL industry.…”
Section: Introductionmentioning
confidence: 99%
“…ESP32 chips are implemented not only in iHealth monitoring systems, but now smart systems are also being developed for the comfort and convenience of mental health and well-being. The article [24] documents a case study of the creation of an intelligent lighting system according to the detection of human emotions. It uses, among other things, necessary hardware components, the predecessor of the ESP32 chip, namely ESP8266, and the already mentioned MQTT communication standard, which is the most common communication standard.…”
Section: Background and Related Workmentioning
confidence: 99%